Research of Ukrainian Fashion Industry Goods Consumers - Pashkevych, K. L.; Kryvonis, N. A.; Vyshnevska, M. O.; Rogotchenko, O. O. (Art and Design, 2019)
To analyze the classifications of modern fashion consumers in accordance with current realities of the fashion industry market for clothing design. The systematic approach to the chosen object of research has been used; the analytical-typological and comparative methods have been applied. The research contains a critical analysis of publications on selected topics and is based on a sociological survey and statistical processing of data. An overview of modern studies has allowed to characterize the behavior of fashion industry consumers and to classify them according to different criteria. The factors influencing the decision of consumers about fashion goods purchasing, the classification of clothing consumers have been analyzed and the purchasing behavior of Ukrainian women as consumers of fashion goods has been investigated. A survey has been conducted in order to study the typology of Ukrainian consumers of fashion industry products. As a result of the survey, it has been found that Ukrainian women buy fashion goods mainly for aesthetic reasons, firstly considering the products design; clothing is a tool for them to look stylish, express themselves and stand out among others. Most women buy clothes in multi-branded shopping malls, and online shopping for fashion goods over the Internet is not popular among Ukrainian women. Ukrainians prefer fashion clothes of foreign manufacturers, only occasionally buying home-made products. The motives and behavioral patterns of fashion industry consumers have been investigated, the factors influencing the purchase decision have been determined, the main characteristics of Ukrainian fashion industry consumers for clothes design have been determined. Modern consumers of fashion industry market have been characterized, the attitude of Ukrainian clothing consumers to shopping and fashion has been determined. The research results can be used to teach subjects related to the theory of fashion and fashion industry.